2016
DOI: 10.1016/j.phrp.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm Properties of Peganum harmala against Candida albicans

Abstract: ObjectivesVaginitis still remains as a health issue in women. It is notable that Candida albicans producing biofilm is considered a microorganism responsible for vaginitis with hard to treat. Also, Peganum harmala was applied as an anti fungal in treatment for many infections in Iran. Therefore, this study goal to investigate the role of P. harmala in inhibition of biofilm formation in C. albicans.MethodsSo, 27 C. albicans collected from women with Vaginitis, then subjected for biofilm formation assay. P. harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…These clinical isolates were collected from the vulvovaginal candida cies in women from the west part of Iran. Results indicated that the extract of P. harmala was capable of inhibiting the biofilm formation in the strong biofilm-forming C. albicans at a concentration of 12 µg/ml, while for the moderate and weak biofilm-forming C. albicans , effective concentrations were 10 and 6 µg/ml [ 6 ]. In this study, we were not able to identify which extract was used by the authors for their experiments as well as their geographic location.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical isolates were collected from the vulvovaginal candida cies in women from the west part of Iran. Results indicated that the extract of P. harmala was capable of inhibiting the biofilm formation in the strong biofilm-forming C. albicans at a concentration of 12 µg/ml, while for the moderate and weak biofilm-forming C. albicans , effective concentrations were 10 and 6 µg/ml [ 6 ]. In this study, we were not able to identify which extract was used by the authors for their experiments as well as their geographic location.…”
Section: Methodsmentioning
confidence: 99%
“…It becomes virulent generally when the patient gets exposed to broad-spectrum antibiotics for a longer duration, chemotherapies as well as dominantly in the immune-compromised patients [ 1 - 5 ]. C. albicans is responsible for 15-20% of the vaginitis cases, which is a very common health issue in women [ 6 , 7 ]. It has also been recorded that out of all Candida spp., C. albicans accounted for more than 42% fungal infections worldwide [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…High dose of Esfand can reduce spermatogenesis in mice [57]. Aboualigalehdari et al [58] revealed that P. harmala as antibiofilm herbal medicine for C. albicans, they have concluded that it seems to be necessary to investigate traditional herbs against pathogenic microorganisms. It has been reported that the seeds contain a red pigment used for coloring wool and carpets and also use as a spice as important aphrodisiac in traditional medicine [39].…”
Section: Medicinal Uses and Potential Health Benefits In Traditional mentioning
confidence: 99%
“…It is applied as a traditional medicine due to its long-lasting antibacterial, fungicide, and herbicide effects. Many authors have reported the inhibitory effects of P. harmala on bacteria, parasites, viruses, and cancer cells (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%